The Influence of Health Counseling on Family Knowledge about Recovery of Pulmonary Tb Patients in The Working Area of Puskesmas Burau - Lestari Lorna Lolo; Romi R S (State Islamic University of Sunan Ampel, 2019)
Pulmonary tuberculosis is a direct infectious disease caused by TB germs (mycobacterium tuberculosis). Health problems experienced by one family member can affect other family members, especially families who care for TB patients known as infectious diseases, so families are required to understand pulmonary TB as a whole. However, families who care for TB patients still lack understanding about recovery of the pulmonary TB patients. The purpose of the study was to analyze the influence of health counseling on family knowledge about recovery of pulmonary TB patients in the working area of Puskesmas. The kind of research is quantitative using the pre-experimental design of one group pre-post test. The subject of research were families who treated TB patients in the working area of Puskesmas Burau. Interventions got by providing health counseling using leaflets. Data collection method used a questionnaire. The results of the study used paired samples T-test with a calculated value for the influence of health counseling on family knowledge about recovery of pulmonary TB patients obtained p-value = 0,000 smaller than the value of p-value = 0.05. From the analysis can be interpreted that Ha is accepted and H0 rejected or there was an effect of health counseling on family knowledge about recovery of pulmonary TB patients. The suggestion of research is suggested to the health center to keep improving the health counseling routines that have been conducted and to modify the counseling method so that TB patients and families are not saturated with the provision of information about pulmonary TB.